A case-control study of risk factors for ischemic heart disease in patients attending tertiary care hospitals in India (South East Asia Journal of Public Health, 2014)
Ischemic heart disease (IHD) is the leading cause of both mortality and forgone healthy years of life among working-age adults (15-69 years) in South Asia. It is the leading cause of death in India and worldwide. For non-communicable diseases (NCDs), common, modifiable and easily measurable risk factors could be reliably used to predict the future burden of the diseases and to measure the effectiveness of public health interventions. A case-control study was undertaken to examine the socio-demographic profile of IHD patients and to identify the risk fac-tors in already diagnosed cases of IHD admitted in three tertiary care hospitals of Ahmedabad, India. We have in-cluded 100 cases and 100 controls who were group matched with the cases. The association of various risk factors with IHD was assessed. On univariate analysis it was found that 7 out of 8 risk factors were significantly associated with IHD. They are alcohol consumption (OR; 14.6, 95% CI; 6.4-33.3), smoking (OR; 13.6, 95% CI; 6.6-27.8), to-bacco consumption in non-smoking form (OR;2.3, 95% CI; 0.78-7.02), hypertension (OR; 6.5, 95% CI; 3.4-12.3), Type 2 diabetes (OR; 4.5, 95% CI; 2.4-8.7), obesity (OR; 9.7, 95% CI; 4.9-19.1), sedentary lifestyle (OR; 3.8, CI; 1.8-8.4 ) and family history (OR; 5.3, 95% CI; 2.8-9.9). This study identified the significance of alcohol, smoking, obesity, Type 2 diabetes, hypertension, sedentary lifestyle and family history in the outcome of IHD. This suggests that the increased cardiovascular risk among the urban population of Ahmedabad city may be preventable through lifestyle interventions along with the judicious use of medicines to attain optimal levels of blood pressure, lipids and glucose among the high risk population. South East Asia Journal of Public Health 2013; 3(1): 57-60 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17712